The plasma proteome reveals distinct signaling pathways associated with PR3-ANCA positive and MPO-ANCA positive vasculitis - Hellbacher, Erik; van Hoef, Vincent; Johansson, Alina; Knight, Ann; Gunnarsson, Iva; Bruchfeld, Annette; Eriksson, Per; Ohlsson, Sophie; Rantapää-Dahlqvist, Solbritt; Dahlqvist, Johanna (Frontiers in Immunology, 2025)
ObjectiveDespite recent advances, the pathophysiological mechanisms underlying anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) remain incompletely understood, and comparative proteomic analyses of AAV subtypes are lacking. This study aimed to identify key molecular signaling pathways activated in AAV and to elucidate molecular distinctions between AAV with proteinase 3 ANCA (PR3-AAV) and AAV with myeloperoxidase ANCA (MPO-AAV).MethodsPlasma samples from 41 cases with active PR3-AAV, 24 with active MPO-AAV and 138 population controls were analyzed for 185 proteins using proximity extension assay and Luminex. Differential expression was assessed between PR3-AAV, MPO-AAV and controls using univariate and partial least squares discriminant analyses. Protein-protein interactions and pathway enrichment were explored using STRING and Cytoscape databases.ResultsCompared with controls, 31 proteins were significantly upregulated in PR3-AAV and 29 in MPO-AAV; 18 were shared, whereas 13 and 11 were specific to PR3-AAV and MPO-AAV, respectively. Shared proteins were enriched in general immune pathways, including IL-6 signaling. AAV subgroup-specific proteins were combined with proteins differentiating between PR3-AAV and MPO-AAV in a direct comparison. MMP-1, MMP-9, HGF, and OSM were uniquely upregulated in PR3-AAV, while TNF, TNF-R1/R2, TNFRSF14, and TNFRSF9 were prominent in MPO-AAV. Functional enrichment analyses underscored STAT3 signaling in PR3-AAV and TNF signaling in MPO-AAV.ConclusionsThis study identifies distinct and shared signaling pathways in PR3-AAV and MPO-AAV, highlighting STAT3 and TNF pathways as potential subtype-specific mechanisms. These findings offer insight into AAV pathogenesis and may guide the development of more targeted, less toxic treatments tailored to AAV subtypes.